Duplication and Diversification of REPLUMLESS – A Case Study in the Papaveraceae - Zumajo-Cardona, Cecilia; Pabón-Mora, Natalia; Ambrose, Barbara A. (Frontiers in Plant Science, 2018)
There is a vast amount of fruit morphological diversity in terms of their texture, the number of carpels, if those carpels are fused or not and how fruits open to disperse the seeds. Arabidopsis thaliana, a model eudicot, has a dry bicarpellate silique, when the fruit matures, the two valves fall apart through the dehiscence zone leaving the seeds attached to the remaining medial tissue, called the replum. Proper replum development in A. thaliana is mediated by REPLUMLESS (RPL), a TALE Homeodomain protein. RPL represses the valve margin genetic program and the downstream dehiscence zone formation in the medial tissue of the siliques and RPL orthologues have conserved roles across the Brassicaceae eudicots. A RPL homologue, qSH1, has been studied in rice, a monocot, and plays a role in fruit shedding making it difficult to predict functional evolution of this gene lineage across angiosperms. Although RPL orthologues have been identified across all angiosperms, expression and functional analyses are scarce. In order to fill the phylogenetic gap between the Brassicaceae and monocots we have characterized the expression patterns of RPL homologues in two poppies with different fruit types, Bocconia frutescens with operculate valvate dehiscence and a persistent medial tissue, similar to a replum, and Papaver somniferum, a poppy with persistent medial tissue in between the multicarpellate gynoecia. We found that RPL homologues in Papaveraceae have broad expression patterns during plant development; in the shoot apical meristem, during flowering transition and in many floral organs, especially the carpels. These patterns are similar to those of RPL in A. thaliana. However, our results suggest that RPL does not have conserved roles in the maintenance of medial persistent tissues of fruits but may be involved with establishing the putative dehiscence zone in dry poppy fruits.